Comparison between Outcome of Harmonic Scalpel and Conventional Hemostasis Method for Removal of Thyroid Gland in Total Thyroidectomy - Muhammad Amir; Abbas, Hassan (Indus Journal of Bioscience Research, 2025)
Objective: To compare the outcomes of harmonic scalpel and conventional suture ligation hemostasis method in patients who underwent total thyroidectomy in terms of intraoperative blood loss, operative time, length of hospital stay and RLN injury. Study Design: Randomize controlled trial. Place and Duration of the Study: Department of General Surgery, Sheikh Zayed Hospital, Rahim Yar Khan, from February 2025 to June 2025. Methodology: Patients scheduled for total thyroidectomy were divided randomly into two groups. In Group A, thyroidectomy was performed using a Harmonic scalpel, and in Group B, hemostasis was accomplished using conventional methods. Baseline demographic data were collected for all subjects. The main operative variables measured were duration of surgery, estimated intraoperative blood loss, length of hospital stay, and occurrence of recurrent laryngeal nerve (RLN) injury. Categorical variables were tested for statistical significance using Chi-square test or Fisher’s Exact test when necessary. Continuous variables were assessed using the independent sample t-test for normally distributed data and the Mann-Whitney U test for non-normally distributed data. The statistical analysis was performed with SPSS version 26.0 and a p value less than or equal to 0.05 was considered as statistically significant. Sample Size: This study was conducted on 60 patients, both male/female, aged 20-60 years, whose total thyroidectomy was planned. Results: Two patients from the harmonic group were excluded intraoperatively due to distorted anatomy requiring conventional hemostasis, leaving 58 patients for analysis (Group A: n=28; Group B: n=30). Mean blood loss was lower in Group A than Group B (69.32 ± 7.37 mL vs 80.60 ± 10.40 mL; p